(untitled) - Mohanty, Pankaj Kumar; Venkatesh, H A; Nagesh, N Karthik; Razak, Abdul (Asian Journal of Clinical Pediatrics and Neonatology, 2014)
Acute liver failure in neonates is incidentally rare with very high mortality in spite of aggressive management. Causes include sepsis, metabolic, hematological, congenital vascular abnormalities and drugs. Early aggressive treatment, multidisciplinary involvement and liver transplantation has some hope in this regard. We are presenting a neonate with acute liver failure who succumbed despite all possible management available.